2017
DOI: 10.1016/j.oceaneng.2017.02.036
|View full text |Cite
|
Sign up to set email alerts
|

2D numerical study of wave and current-induced oscillatory non-cohesive soil liquefaction around a partially buried pipeline in a trench

Abstract: This paper proposes a two-dimensional (2D) coupled model for wave and currentseabed-pipeline interactions to examine oscillatory non-cohesive soil liquefaction around a partially buried pipeline in a trench. Unlike previous studies, two new features are included in this model: (1) wave-current interactions around the pipeline; and (2) fully coupled processes for the wave and current-seabed-pipeline system. In this study, the Reynolds Averaged Navier-Stokes (RANS) equations are applied to simulate the flow fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…In this study, the length of the computational domain (l) is set to be three times the wavelength to ignore the influence of lateral boundaries. [25] and three-dimensional [26] numerical simulation to study the wave-current induced soil liquefaction around the buried pipeline. However, in their research, only the oscillatory soil response under a wave and current loading have been determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the length of the computational domain (l) is set to be three times the wavelength to ignore the influence of lateral boundaries. [25] and three-dimensional [26] numerical simulation to study the wave-current induced soil liquefaction around the buried pipeline. However, in their research, only the oscillatory soil response under a wave and current loading have been determined.…”
Section: Methodsmentioning
confidence: 99%
“…e max − e e max − e min (25) As seen in Equation 17, when there is a change in the relative density of the soil, both the empirical coefficient α r and β r in the source term f (x, z, t) varies, which eventually leads to different values of residual pore pressure. Figure 6 shows the generation of oscillatory and residual pore pressure due to the influence of various relative density (D r = 0.2, 0.3 and 0.5) over a certain period at point x = 50 m and z = -10 m. In this section, the soil permeability (k) and shear modulus (G) are set as 1.0 × 10 −4 m/s and 5.0 × 10 6 N/m 2 respectively while other parameters remain unchanged as shown in Table 1.…”
Section: Effects Of Relative Densitymentioning
confidence: 99%
“…The advantage of this approach is simple and identical to previous closed-form analytical solu-tions for fine sand, but significant differences were found for coarse sand (Hsu and Jeng, 1994). Based on the quasi-static (QS) model, some numerical models are established to study the soil response around the pipelines (Duan et al, 2017b) and breakwaters (Liao, Tong, and Chen, 2018;.…”
Section: Quasi-static Modelmentioning
confidence: 99%
“…Field observations of some project cases have shown that wave loads do not usually cause direct damage to the strength or stiffness of an offshore structure but they often lead to the seabed liquefaction of the region that surrounds the offshore structure and subsequently result in the partial or total loss of bearing capacity [5][6][7][8]. Pile foundations, pipelines and breakwaters have received great attention in the study of wave-seabed-structure interactions [9][10][11], whereas cofferdams have been neglected in such investigations. Therefore, the study of the wave-induced seabed response around cofferdams is of great significance to the safety control during civil engineering construction.…”
Section: Introductionmentioning
confidence: 99%